Triglyceride to high-density lipoprotein cholesterol ratio and total cholesterol to high-density lipoprotein cholesterol ratio and risk of benign prostatic hyperplasia in Chinese male subjects - Zhu, Chen; Wu, Juan; Wu, Yixian; Guo, Wen; Lu, Jing; Zhu, Wenfang; Li, Xiaona; Xu, Nianzhen; Zhang, Qun (Frontiers in Nutrition, 2022)
Lipid metabolism disorders contribute to the risk factor of prostatic hyperplasia. Lipid ratios have also attracted a lot of attention. Yet, research about the correlation of lipid ratios with prostatic hyperplasia is limited. Hence, the aim of this study was to investigate the association of lipid ratios with the risk of benign prostatic hyperplasia (BPH) in Chinese males. Healthy men who underwent routine health check-ups from January 2017 to December 2019 were recruited. 24,962 individuals were finally enrolled in this research. Binary logistic regression analysis was performed to investigate the relationship between lipid ratios and BPH in Chinese adults. Results: After health examinations for more than 2 years, 18.46% subjects were ascertained as incident BPH cases. Higher age, body mass index (BMI), prostate specific antigen (PSA), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, total cholesterol to high-density lipoprotein cholesterol (TC/HDL-C) ratio and lower high-density lipoprotein cholesterol (HDL-C) were significantly associated with BPH risk, while total cholesterol (TC) was not significant. When quartiles of TG/HDL-C and TC/HDL-C were analyzed in multivariable model, higher TG/HDL-C and TC/HDL-C were associated with a risk of BPH [odds ratio (OR) = 2.11; 95% confidence interval (CI): 1.89, 2.36; P-trend < 0.001; and OR = 1.67; 95% CI: 1.50, 1.85; P-trend < 0.001, respectively]. In addition, stratified analyses based on general population exhibited that with increasing age (≥ 35 years) the relationship of TG/HDL-C ratio with BPH risk was dominantly positive (all P-trend < 0.001, P-interaction = 0.001), and significant associations were also found in blood pressure strata and FBG strata (all P-trend < 0.001), except men with BMI ≥ 28Kg/m2 was slightly weakened (OR = 2.01, 95%CI: 1.41, 2.85; P-trend = 0.04). On the other hand, there were significant associations between quartiles of TC/HDL-C and risk of BPH were observed mainly in age 55-64 years, BMI 18.5-23.9 Kg/m2, blood pressure strata, FBG strata. However, the P value for a linear trend among those with BMI ≥ 28 Kg/m2 in which participants at the highest quartile of TC/HDL-C had an OR of 1.45 (95% CI: 1.09, 1.93) was 0.594.